Contingent valuation of road traffic noise: A case study in China. (April 2021) - Ma, Hui; Wen, Mengjun; Xu, Lijun; Zhang, Ziya
Highlights: The % highly annoyed people rapidly increased with the exposure to road traffic noise. Contingent valuation method was used to quantify economic value of noise control. The residents' willingness to pay increased with noise exposure level nonlinearly. The results can be useful in policy making, noise management and products developing. Abstract: It is necessary to conduct an economic valuation of noise control to justify the high potential costs of traffic noise mitigation. This study was based on a combined social survey on community responses to road traffic noise and contingent valuations of noise reduction in China. The results showed that the number of highly annoyed people increased rapidly with exposure to road traffic noise, particularly when the exposure level exceeded 70 dBA. The average amount of money that households were willing to pay to reduce the noise was 162.64 RMB. The residents' willingness to pay (WTP) was affected significantly by their annoyance level and three other factors, namely, age, income, and the noise prevention method used before. The residents' WTP increased non-linearly with noise exposure level: at 55 dBA, the average WTP for a 1 dB reduction was about 2.12 RMB per household and about 4.74 RMB at 70 dBA.